Alterações laboratoriais em felinos domésticos positivos para Leishmania spp. no município de Araguaína, Tocantins - Silva, Paulo Roberto Pinheiro da (2024)
Leishmaniasis is a zoonosis, with a worldwide distribution that can affect humans, as well as several species of both wild and domestic animals, in different regions of the world. Characterized as an infectious process caused by several species of Leishmania, transmission occurs through the bite of female sandflies belonging to the genera Lutzomyia when infected. The appearance of lesions and clinical signs in dogs and cats is linked to the immune response, with the Th1 response being the most efficient in felines. Therefore, the present work aims to verify laboratory changes in cats positive for leishmaniasis, diagnosed through cPCR in whole blood samples, in the municipality of Araguaína-TO. Positivity for Leishmania spp was confirmed by conventional PCR. Blood and serum samples were collected, and hematological and biochemical tests were performed on eight positive cats. All animals presented erythrocyte and leukocyte count values within normal limits. Hypoalbuminemia, followed by hypoproteinemia were the most frequent biochemical changes. This study contributes to the knowledge regarding feline leishmaniasis and laboratory changes resulting from parasitism. It exposes the importance of clinical evaluation of felines as susceptible hosts to Leishmania spp. in veterinary routine in endemic regions.